Effect of Foliar Applied Potassium and Cytokinin On Some Growth Parameters Of Lentil Plant (Lens culinaris Medic.). - Al- Kazzaz, A. G. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experiment was conducted in the glasshouse of Biology Dept. ,College of Education Ibn- Al- Haitham ,University of Baghdad, during the growing season(2011), to study the effect of sprying potassium sulphate at (0,200,400,600) ppm and cytokinin at (0,75,150)ppm and their interactions on number of branches , protein percentage , carbohydrate percentage , absolute growth rate , biomass duration , relative efficiency of fertilizer and value of the secondary productivity ,in Lentil plant cultivar(Baraka). Results indicated that foliar sprying of potassium sulphate and cytokinin and their interactions gave a significant effect on all vegetative growth parameters of lentil plant. the concentration600 ppm of potassium sulphate and the concentration150 ppm of cytokinin gave the highest values of absolute growth rate , and the concentration 400 ppm of potassium sulphate and the concentration 150 ppm of cytokinin gave the best values of protein percentage , carbohydrate percentage ,biomass duration and relative efficiency of fertilizer, also the concentration 600 of potassium sulphate and the concentration 75 ppm of cytokinin gave the best values of number of branches and the value of the secondary productivity.